Pavement technology elements in green highway - Wan Azahar, Wan Nur Aifa; Hainin, Mohd Rosli; Abd. Majid, Muhd Zaimi; Mohamad Zin, Rosli; Yaacob, Haryati; Zakaria, Rozana; Bujang, Mastura (UTM Press, 2015)
A technology that has been experienced during the construction of a pavement has indicated the improvement in exploring the advanced technology pavement. Types of technologies of pavements applied are always related to the high performance of the pavements during the life span. Indeed, the application of technology in pavement has insisted to reduce the rate of environmental problems such as global warming, abundance of solid waste and so on. The development of technologies in pavement has been identified by the expert in highway engineering as one of the initiatives in response the sustainability requirement that later on will be applied to implement green highway concepts. Nowadays, the process of selecting a variety of green pavement technology element is becoming more challenging to be evaluated qualitatively. This paper aims to determine critical pavement technology element based on ranking of priority to achieve the objective of the green highway design. It is necessary to determine the critical elements in order to identify which elements will most contribute to the green practices based on the priority level of the weighted factor value. Therefore, a questionnaire survey was developed and distributed to the respondent in order to obtain the agreement level for the element. Based on the weighted analysis, it has been shown that the soil erosion control element has achieved first ranking in order to implement green highway and followed by permeable and cool pavement.In conclusion, the identification of critical elementsof green pavement technology is the main key towards sustainable development in the future.